Respuesta :
Answer:
4t^2 - 32t + 64.
Step-by-step explanation:
f(x) = 4x2 – 8x + 4
f(t - 3) = 4(t - 3)^2 - 8(t - 3) + 4
= 4(t^2 - 6t + 9) - 8t + 24 + 4
= 4t^2 - 24t + 36 - 8t + 28
= 4t^2 - 32t + 64.
The value of f(t – 3) when the function f(x) = 4x2 – 8x + 4 is f(t – 3) =4t²–32t+64.
What is a Function?
A function assigns the value of each element of one set to the other specific element of another set.
The value of f(t – 3) when the function f(x) = 4x2 – 8x + 4 will be,
f(x) = 4x² – 8x + 4
f(t – 3) = 4(t – 3)² – 8(t – 3) + 4
f(t – 3) = 4(t² + 9 –6t) – 8t + 24 + 4
f(t – 3) = 4t² + 36 – 24t – 8t + 24 + 4
f(t – 3) = 4t² + 36 – 32t + 24 + 4
f(t – 3) = 4t² – 32t + 64
Hence, The value of f(t – 3) when the function f(x) = 4x2 – 8x + 4 is f(t – 3) =4t²–32t+64.
Learn more about Function:
https://brainly.com/question/5245372
#SPJ2